Hodgson, Vet al ed (2014) The design, experience and practice of networked learningSpringer (Berlin) isbn 978‐3‐319‐01940‐6 281 pp £93.50 e‐book (boards £117) http://www.springer.com/education+%26+language/learning+%26+instruction/book/978‐3‐319‐01939‐0. (November 2014) - Johnson, Mike
Summary This collection of twelve papers from the 2012 Networked Learning Conference will stimulate and focus your attention on vital aspects of the design, experience, practice and research of networked learning in a diverse range of contexts. An extended introductory overview chapter carries a valuable contribution to debates about the essence and state of the field. If you are likely to find the content of this book relevant, I recommend you borrow a copy. Mike Johnson